Analisa Cacat yang Terjadi pada Proses Pembuatan Roda Gigi Lurus Melalui Proses Pengecoran Besi Cor Nodular yang Menggunakan Chill - Natalino Fonseca D.S. Guterres (ROTASI, 2022)
Gear surface hardening by using chill in the casting method is very unique in the gear manufacturing process because it shortens the stages of gear manufacturing. The problem that needs attention is the occurrence of defects in the tooth profile after the gears are cast. Porosity defects and shrinkage or expansion defects often occur in the final solidification step in nodular cast iron materials. The use of chill is a fast cooling rate on the surface between the cast and molded material. However, it is easy for air bubbles to occur in the process of forming spheroidal graphite at the end of the solidification step. The purpose of this study was to analyze shrinkage or expansion defects and porosity defects that occur on the tooth profile surface. Casting uses an electric furnace at a temperature of 1400oC and an open mold using silica sand. Before the pouring step, the chill will be heated at a temperature of 700oC. Dimensional change defects are detected by measuring the dimensions of the tooth profile. While the porosity defects were tested by radiography to determine the cavities in the chilled area, then the percentage value of porosity used the pycnometric method and the Archimedes principle. Shrinkage defects in the tooth thickness area are on average 0.2mm (0.04%), while porosity defects in chilled areas are cavities in the surface area of the tooth profile having the highest porosity value reaching 0.108wt.% because it is influenced by Cooling speed too high.